Changes in the deep subsurface microbial biosphere resulting from a field-scale CO2 geosequestration experiment - Mu, Andre; Boreham, Chris; Leong, Henrietta X.; Haese, Ralf; Moreau, John W. (Frontiers in Microbiology, 2014)
Subsurface microorganisms may respond to increased CO2 levels in ways that significantly affect pore fluid chemistry. Changes in CO2 concentration or speciation may result from the injection of supercritical CO2 (scCO2) into deep aquifers. Therefore, understanding subsurface microbial responses to scCO2, or unnaturally high levels of dissolved CO2, will help to evaluate the use of geosequestration to reduce atmospheric CO2 emissions. This study characterized microbial community changes at the 16S rRNA gene level during a scCO2 geosequestration experiment in the 1.4 km-deep Paaratte Formation of the Otway Basin, Australia. One hundred and fifty tons of mixed scCO2 and groundwater was pumped into the sandstone Paaratte aquifer over 4 days. A novel U-tube sampling system was used to obtain groundwater samples under in situ pressure conditions for geochemical analyses and DNA extraction. Decreases in pH and temperature of 2.6 log units and 5.8°C, respectively, were observed. Polyethylene glycols (PEGs) were detected in the groundwater prior to scCO2 injection and were interpreted as residual from drilling fluid used during the emplacement of the CO2 injection well. Changes in microbial community structure prior to scCO2 injection revealed a general shift from Firmicutes to Proteobacteria concurrent with the disappearance of PEGs. However, the scCO2 injection event, including changes in response to the associated variables (e.g., pH, temperature and salinity), resulted in increases in the relative abundances of Comamonadaceae and Sphingomonadaceae suggesting the potential for enhanced scCO2 tolerance of these groups. This study demonstrates a successful new in situ sampling approach for detecting microbial community changes associated with an scCO2 geosequestration event.